Analisis Efektivitas Pemberian Rebusan Daun Sirih terhadap Waktu Penyembuhan Luka Perineum - Dian Eka Nursyam; Sandra Ilona (Poltekkes Kemenkes Padang, 2025)
The 2017 Indonesian Demographic and Health Survey (SDKI) reported that the leading causes of postpartum maternal mortality are bleeding (30%), infection (22.5%), and eclampsia (2.0%). Postpartum hemorrhage occurs in 49% of mothers, caused by retention, perineal rupture, and retained placenta. Before using green betel leaf decoction, 16 mothers (51.6%) had a degree 0 perineal wound, while after treatment, this increased to 26 mothers (83.9%).This study aims to determine the effectiveness of betel leaf decoction on perineal wound healing at BPM Hj. Yetti Latif, S.ST, Padang Pariaman, in 2023. It employs a quasi-experimental design, conducted from January to April, with 30 postpartum mothers selected through consecutive sampling. Data collection used a questionnaire, and analysis was performed using univariate and bivariate methods, with the Chi-Square test for hypothesis testing.The results show a p-value of 0.003 (α = 0.05), indicating a significant effect of betel leaf decoction on wound healing. Since p-value (0.003) < 0.05, H₀ is rejected, confirming the effectiveness of betel leaf decoction in accelerating perineal wound healing. This study concludes that betel leaf decoction is an effective natural remedy for postpartum perineal wound healing. Postpartum mothers are encouraged to use betel leaf decoction to promote faster recovery.